1970
DOI: 10.1099/00221287-63-2-249
|View full text |Cite
|
Sign up to set email alerts
|

Division of Mycoplasmas into Subgroups

Abstract: S U M M A R YThe deoxyribonucleic acid (DNA) base compositions of 12 recently isolated or new species of mycoplasmas fell within the range known for the Mycoplasma group. By DNA-DNA hybridization a new sterol-nonrequiring strain, S-743, was unrelated to Mycoplasma laidlawii or M . granularum, the latter two strains showing moderate cross-reactivity ; swine strain B 3 appeared to be related to M . mycoides var. Capri. From these results and information in the literature, the mycoplasmas have been divided into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…A sister group relationship between the M. mycoides and Spiroplasma apis clusters was supported by 22 positions of this same type. Even the stricter definition yielded three synapomorphies that supported this particular association.…”
Section: Mandwr Group Exhibit This Characteristic (Except For the Lactomentioning
confidence: 75%
See 1 more Smart Citation
“…A sister group relationship between the M. mycoides and Spiroplasma apis clusters was supported by 22 positions of this same type. Even the stricter definition yielded three synapomorphies that supported this particular association.…”
Section: Mandwr Group Exhibit This Characteristic (Except For the Lactomentioning
confidence: 75%
“…Early attempts to subdivide the mycoplasmas, by using immunological approaches, DNA compositions, and the like, proved to be taxonomically useful but gave little phylogenetic information (22,35). On the other hand, rRNA sequences reveal the phylogeny of this group in considerable detail.…”
mentioning
confidence: 99%
“…The theoretical number of restriction sites for a restriction enzyme with a 6-base recognition sequence can be calculated on the basis of base composition (G+C = 29 mol% in M. hominis [28]) and genome size (M. hominis genome, -700 kb). BamHI, Sall, and XhoI were thus calculated to cleave the genomes 39 times, and SmaI and ApaI cleaved it 7 times.…”
Section: Discussionmentioning
confidence: 99%
“…Neimark (1970) higher GC ratio than most avian species, 32-36%, and are also antigenically distinct. Many of the avian strains were tested by Kelton and Mandel (1969), and since some of their cultures were later found to be mixed, some of their data may not be valid (M. L. Frey, personal communication).…”
Section: Use Of Guanosine Plus Cytosine Content In Classificationmentioning
confidence: 89%
“…The work of McGee et al (1967), using the agar column method, showed the reverse, that is, the percent homology was higher (72-90%) when A. laidlawii B was Immobilized than when A. laidlawii B was immobilized (60-67%), suggesting that B DNA was larger. ^ laidlawii A was found to be 33% related to A. qranularum but only 3-6% to another acholeplasma strain s-743 (Neimark, 1970). The s-743 strain was 6% related to the avian strain M. gallisepticum S 6.…”
Section: Hybridization Experiments With Mycoplasmamentioning
confidence: 92%